Өнер объектілері Орталық Азияда қоршаған ортаны қорғау құралы ретінде - Makenov, T.; Moldasheva, A.; Sariyeva, A. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2023)
research results in identifying the significance of the influence of environmental art objects on people’s consciousness and their awareness of the seriousness and scale of environmental problems in their region of residence (Central Asia). In addition, a graphical representation of the described art objects was used. As a result, it is concluded that it is possible to note a general trend emerging in the field of creating environmental art objects in Central Asian countries: the examples presented were created by activists and artists as part of a certain large-scale program or action to protect the environment, or within a certain art festival. Despite the small number of art objects of environmental themes, it is possible to note their specific orientation, directly related to the problems of the region (cutting down of saxaul) or a certain area (the Aral Sea). Along with the importance of developing strategic actions to address issues of environmental protection and protection in Central Asia, one of the primary tasks remains to attract public attention to environmental problems, both on a global scale and in more local aspects. Art has always been one of the most effective forms of reflection of actual and pressing social problems. Today, artists and creators using such a direction as eco-art have the opportunity to attract the attention of the broad masses of the population of Central Asia to the environmental problems unfolding in the countries of the region. At the same time, eco-education and eco-education with the use of various forms of art, including the practice of creating art objects, should be considered as a promising direction. Key words: Central Asia, art projects, eco-art, installation, Aral Sea, ecological art, artists.